Visual healing in visual communication design: Exploring calm aesthetics for the psychological well-being of urban society - Lestari, Siti Indah; Ramadhani, Ivo (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2026)
This study investigates the concept of visual healing from a Visual Communication Design (VCD) perspective, focusing on its potential contribution to emotional comfort and psychological well-being among urban office workers. Contemporary workplace environments are increasingly characterized by prolonged screen exposure, dense visual information, and sustained cognitive demands, conditions that intensify visual fatigue and psychological strain. In this context, the study positions visual design not merely as an aesthetic practice, but as a psychologically responsive medium capable of shaping users' emotional experiences in everyday work settings. Employing a qualitative Research through Design (RtD) methodology, the study treats the design process as a reflective and epistemic mode of inquiry to explore the relationship between visual design elements and users' emotional responses. A series of visual communication design artefacts was developed based on calm-oriented visual principles, including soft colour palettes, the strategic use of negative space, balanced visual rhythm, and lightweight typography. These artefacts were evaluated through visual perception testing involving 20 urban office workers in Medan, Indonesia. The findings reveal consistent descriptive tendencies indicating enhanced perceptions of visual comfort, calmness, focus, and emotional relaxation. Although the designs do not function as clinical or therapeutic interventions, the results suggest that deliberately structured visual stimuli may operate as supportive, non-invasive restorative experiences within visually intensive work environments. Based on these findings, the study proposes the Visual Healing Framework as a conceptual model that elucidates the interaction between visual design elements and emotional responses in urban workplace contexts.